The Effect of Financial Literature and Islamic Work Motivation on the Performance of Food Micro, Small and Businness Enterprises (MSMEs) in Makassar City - Adiningrat, Andi Arifwangsa; Ruhayu, Yuyu; Rustan, Rustan; Wahyuni, Sri; Fitrianti, A.Nur (Budapest International Research and Critics University, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the business sectors that can encourage economic growth. But in reality, MSMEs have various problems, namely the problem of financial and non-financial limitations. In addition, there are challenges faced by MSMEs, such as increasingly fierce competition requiring competent resources. This study aims to determine the effect of financial literacy and Islamic work motivation on MSME performance. This research is multiple regression analysis. The population and sample in this study were 7 Food SMEs in Makassar City. Data collection techniques are documentation, interviews and questionnaires. The data analysis technique in this study is quantitative using multiple regression analysis used to examine the effect of independent variables (financial literacy and Islamic work motivation) on the dependent variable (SME performance). The results showed that partially financial literacy had a positive and significant effect on the performance of MSMEs, while Islamic work motivation had a negative and insignificant effect on the performance of MSMEs.